TAFSIR AYAT-AYAT PENDIDIKAN Nilai-Nilai Pendidikan Q.S. Al-Alaq Ayat 1-5 (Studi Tafsir Al-Misbah Karya M.Quraish Shihab) - Dozan, Wely (STAI Ma'had Aly Al-Hikam Malang, 2020)
Education is one of the efforts to develop intellect and build a character that is Qur'anic. In line with some previous thought research, a reconstruction of Islamic education has been carried out. However, in reality this is still ongoing to be carried out by some thoughts even to the Indonesian interpreter M. Quraish Shihab contributing to provide Qur'ani Values and contextualization through the QS Interpretation. Al-Alaq Verses 1-5 related to this education. Specifically in the interpretation can be formulated into several aspects, First, Educational Values in principle can never be separated from reading. Second, education in principle can direct the Islamic authority that is God, Education in principle is supported by a variety of models and learning methods, namely some Islamic approaches. Third The values of education in principle lead to the phosphitive thing that is insan al-kamil which is implemented and actualized in the education. The research approach is a literature study approach to find the concepts and values of education in al-Misbah's interpretation and is supported by various references, articles, journals, books and so on. Thus, it can be concluded that the values of education that become an urgent subject in learning that is, reading, evaluating, having Islamic authority, providing examples and motivation in learning